(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article investigates the effectiveness of specific didactic conditions and a three-stage developmental model in fostering students’ intercultural communication competence (ICC). The study employs a mixedmethods approach, combining quantitative and qualitative data to provide a comprehensive understanding of the research problem